2010
DOI: 10.1371/journal.pbio.1000484
|View full text |Cite
|
Sign up to set email alerts
|

A Key Commitment Step in Erythropoiesis Is Synchronized with the Cell Cycle Clock through Mutual Inhibition between PU.1 and S-Phase Progression

Abstract: During red blood cell development, differentiation and cell cycle progression are intimately and uniquely linked through interdependent mechanisms involving the erythroid transcriptional suppressor PU.1 and the cyclin-dependent kinase inhibitor p57KIP2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
223
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(244 citation statements)
references
References 64 publications
21
223
0
Order By: Relevance
“…CD71 + Ter119 − proerythroblasts represent a critical transitional stage marked by Epo dependency (51) and elevated DNA replication (45), both shown here to require high LMO2 protein expression. Conversely, terminal erythroid differentiation to the CD71 − Ter119 + stage is necessarily coordinated with growth arrest (13, 51), which we now show to be favored by Lmo2 downregulation, in agreement with previous work indicating that LMO2 overexpression prevents terminal erythroid differentiation (11).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…CD71 + Ter119 − proerythroblasts represent a critical transitional stage marked by Epo dependency (51) and elevated DNA replication (45), both shown here to require high LMO2 protein expression. Conversely, terminal erythroid differentiation to the CD71 − Ter119 + stage is necessarily coordinated with growth arrest (13, 51), which we now show to be favored by Lmo2 downregulation, in agreement with previous work indicating that LMO2 overexpression prevents terminal erythroid differentiation (11).…”
Section: Discussionmentioning
confidence: 85%
“…Cell cycle is highly regulated in the erythroid lineage because ∼80% of primary proerythroblasts (E1 stage; Fig. 3A) are in S phase, exactly at the onset of erythropoietin (Epo) dependence (45), and this proportion sharply drops at the E3 and E4 stages of terminal differentiation. We observed that the E1 population segregated into cells with high and low endogenous LMO2 protein levels (Fig.…”
Section: Lmo2 Expression Levels Control the Rate Of Dna Synthesis Andmentioning
confidence: 99%
“…In particular, it has been shown that the downregulation of p57 Kip2 (and the S-phase entry) commits the cells to erythropoietic differentiation, which is associated with the onset of erythropoietin dependence, activation of GATA-1 (a key erythroid transcriptional regulator), and a switch of chromatin conformation at the b-globin locus toward an active status. These findings identify an important role of p57 Kip2 as a master regulator of erythrocytic differentiation, distinct from its activity as a CDK inhibitor (98).…”
Section: P57 Kip2 Metabolismmentioning
confidence: 86%
“…It was recently shown that a novel linkage exists between cell cycle progression and red blood cell commitment, and that it occurs several cell division cycles before the exit from the cell cycle (98).…”
Section: P57 Kip2 Metabolismmentioning
confidence: 99%
“…The downregulation of PU.1 was reported to play a role in the pathogenesis of various hematological malignancies, including Acute Myeloid Leukemia (AML) [2], multiple myeloma [3] and Myelodysplastic Syndrome (MDS) [4]. PU.1 is also normally present in immature erythroid cells [5], and several reports have indicated that their downregulation is required for erythroid terminal differentiation [6][7][8][9].…”
mentioning
confidence: 99%